2014
DOI: 10.1017/s1478951514000625
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to find meaning in life among spouses of people with ALS

Abstract: Meaning in life strengthened spouses' well-being and ability to find pleasure in a difficult situation. It also strengthened their will to live after the partner's death. Limitations and isolations were strong predictors of what could impair their well-being and the possibility of finding meaning after the partner's death. Spouses need individual support throughout the disease process and after the partner's death, to give them the strength to find meaning in life and prioritize what is important for them. Pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…In the present study and in three previous studies , we have examined the three components of SOC. There is a lack of qualitative studies examining SOC in ALS, especially comprehensibility.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study and in three previous studies , we have examined the three components of SOC. There is a lack of qualitative studies examining SOC in ALS, especially comprehensibility.…”
Section: Discussionmentioning
confidence: 89%
“…SOC is an important factor in maintaining health, and from a salutogenic viewpoint, a person should not be seen as just healthy or sick, but rather as being in a multidimensional continuum between health and ill‐health . Earlier studies have examined manageability and meaningfulness , while this study examines the comprehensibility. The dimension comprehensibility describes the extent to which a person experiences internal and external stimuli as rationally understandable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the participants had not experienced extreme mourning and could recover from their grieving. A study by Ozanne, Graneheim, and Strang (2015) found that the spouses of demanding people with chronic neuromuscular disease were mourning and struggling in finding meaning in life after the partner's death. A study in Japan noted that the severe grief reaction of the family depended on the quality of dying and death and a peaceful death (Tatsuno, Yamase, & Yamase, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in Sweden (43) revealed that family caregivers' distress about the prognosis of the person with ALS made them reluctant to seek support from healthcare services. Qualitative and mixedmethods studies undertaken in the UK (44)(45)(46)(47), Australia (48), Italy (49) and Germany (50), identified that family caregivers and patients would have preferred more support (including diagnostic care, home care, counselling, assistive and adapted equipment, respite care and bereavement care) than that which had been offered to them (44)(45)(46)(47)(48)(49)(50).…”
Section: Support Seekingmentioning
confidence: 99%
“…Qualitative investigations have centred on the overall experience of living with ALS and/or experience of care(8,33,43,45,47,48,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) in addition to decision making in different domains of care(18- 25,34,35,40,41,44,50,62-64). Of the quantitative and mixed-methods studies extracted(11-17,26-32,36- 39,42,46,49,51), approximately half of them focused primarily on decision making in care(13,14,16,27- 29,31,36-39).…”
mentioning
confidence: 99%